UJI AKTIVITAS ANTIFUNGI BAKTERI ASAM LAKTAT ASAL DADIH TERHADAP Aspergillus flavus - Olvaria Misfa; Viola Anggraini Asrizal; Eliya Mursyida; Uly Astuti Siregar (LPPM Universitas Abdurrab, 2023)
Primary gastrointestinal aspergillosis (AGP) is an inflammation of the gastrointestinal tract from the duodenum to the rectum. Aspergillus flavus (A. flavus) is one of the fungi that causes aspergillosis. This infection occurs due to aflatoxin from A. flavus which can cause damage to the gastric mucosa. The use of antifungals for long-term treatment can cause toxicity effects and also resistance, so alternative treatments are needed. Dadih is a fermented product of buffalo milk which contains lactic acid bacteria (LAB). Lactic acid bacteria produce acetic acid, lactic acid, and bacteriocin which can inhibit the growth of the fungus A. flavus. LAB species capable of suppressing the growth of A. flavus were Lactococcus lactis, Lactobacillus casei subsp. pseudoplantarum and Lactobacillus plantarum, and Lactobacillus brevis. To determine and analyze the antifungal activity of lactic acid bacteria from curd against Aspergillus flavus. This study used a post test-only design with a control group. The sample used was LAB isolate from curd, while the test fungus used was A. flavus. This study begins with rejuvenation of LAB isolates, then classification of LAB and pathogens, as well as inhibition test using the well diffusion method. The data obtained were analyzed using One-Way ANOVA test and Bonferroni Post hoc test.: LAB isolates from curd were Gram-positive bacteria in the form of bacilli and cocobasil, with negative catalse test results. The average diameter of the inhibition zones of LAB 1, LAB 2, and LAB against A. flavus were 8.55mm, 10.23mm, and 6.20mm. The results of the ANOVA test showed that there was a significant difference between the three LABs. The results of the Bonferron Post hoc test showed that there was a significant difference between LAB 2 isolates and positive controls against LAB 3. Meanwhile, there was no significant difference between LAB 2 and BAL 3 isolates against LAB 1 isolates. LAB isolate from curd was able to inhibit the growth of the fungus A. flavus.